The Importance of Risk and Subgroup Analysis of Nonparticipants in a Geriatric Intervention Study. (30th June 2016) - Rosted, Elizabeth; Poulsen, Ingrid; Hendriksen, Carsten; Wagner, Lis
Abstract : Background . A major concern in intervention studies is the generalizability of the findings due to refusal of intended participants to actually take part. In studies including ill older people the number of those declining to participate may be large and the concern is therefore relevant. Objectives . To compare patients characteristics, rates of acute readmission, and mortality after one and six months among older persons who agreed and those who declined to participate in a randomized controlled trial and to describe subgroups of nonparticipants. Design . Comparative study based on a randomized controlled trial. Setting . University hospital in the Capital Region of Denmark. Participants . Patients ≥70 years discharged home after a short Emergency Department stay. 399 were requested to participate; 271 consented, whereas 128 refused. Results . Refusers were more likely to be readmitted (p < 0.001 ) or die (p = 0.006 ). The largest subgroup of refusers described as "too ill" had the highest risk of readmission (OR = 3.00, 95% CI = 1.61–5.47, p = 0.001 ) and of mortality within six months (OR = 3.50, 95% CI = 1.64–7.49, p = 0.002 ). However, this seems not to have affected the results of our randomized study. Conclusion . We recommend that intervention studies among older people or other fragile patient groups include analysis of relevant risk and subgroup analyses of refusers.